O Grupo Escolar José Emílio de Aguiar: um capítulo da história da educação primária de Coromandel-MG (1961-1971) - Alves, Suzele Sany Lacerda (2020)
This dissertation is the result of research in the area of Education and in the subarea of History of Education, whose theme focuses on the history of school institutions, being developed in the Graduate Program in Education (UFU) in the History and Historiography of Education. The main objective was to investigate the process of creation and implementation of the José Emílio de Aguiar graduate prime school, part of the historical constitution of Coromandel's primary education and the verification of its social representation from the analysis of the constitutive aspects of the school's identity nature. The period of analysis was established between 1961, the first year of operation of the school, and 1971, due to the extinction of the nomenclature School Groups through the Decree-Law no. 5,692, of August 11 of the same year. The generating problem of this research was to understand which demands constituted local interests for its creation and what was the place and the social representation of the institution from 1961 to 1971 for the city of Coromandel. From the problematization came the hypothesis that the school was created to meet the demand for vacancies of students with low socioeconomic and cultural capital. The theoretical framework that supports this work is based on Souza (1998; 2014), Faria Filho (2014), Vidal (2006), Nosella and Buffa (2009), Araújo (2006; 2012), among others. This is a qualitative research of documentary, empirical and bibliographical nature, which used several sources, such as minutes of school installation, enrollment book, final results book, employees' term of office, employees' time register book, newspapers, photographs and semi-structured interviews. In general, it was noticed that the José Emílio de Aguiar graduate prime school, the third school in the city, was created with the purpose of supplying the needs of places for urban primary education, since, before its actual creation, it functioned as an annex to Coromandel's first school, accommodating two classrooms. After noting, among many aspects, the low educational level of the students' parents, who had professions also of low social prestige, which outlined the profile of students from impoverished families and also noted the precariousness of the modest building where the school operated during this period, the results indicated that the constitutive aspects of the school corroborated the formation of a social distinction that contributed to the crystallization of the concept and representation that the José Emílio de Aguiar graduate prime school was the school of impoverished children.